Dampak Teknik Evaluasi Psikomotorik Terhadap Perolehan dan Retensi Keterampilan Praktis Siswa dalam Konteks Pendidikan Karakter - Adriani, Ayu; Samsinar (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to analyze the impact of psychomotor evaluation techniques on students' acquisition and retention of practical skills, particularly in the context of character education. This research employs a literature review utilizing primary sources. The methods used include systematic literature identification and selection by formulating comprehensive keywords to search for articles, books, and research reports from various online databases. Data collection is conducted through systematic information extraction such as main concepts, theories, and findings from previous research. Information is recorded using a synthesis matrix or reference aid. Data analysis involves data reduction, data presentation, analysis, synthesis, and drawing conclusions. The study results show that psychomotor evaluation significantly affects practical skills. This domain, with its various levels (from imitation to mechanism), is greatly influenced by cognitive and affective aspects, emphasizing the need for holistic evaluation. Effective evaluation techniques, such as observation, rubrics, and portfolios, play a crucial role in identifying strengths/weaknesses, providing specific feedback, motivating students, adjusting learning strategies, measuring progress, and determining levels of mastery. Therefore, the proper application of psychomotor evaluation ensures that students are not only knowledgeable but also able to apply it in real life